Effects of trawling activity on the bamboo-coral Isidella elongata and the sea pen Funiculina quadrangularis along the Gioia Canyon (Western Mediterranean, southern Tyrrhenian Sea) - Pierdomenico, Martina; Russo, Tommaso; Ambroso, Stefano; Gori, Andrea; Martorelli, Eleonora; D'Andrea, Lorenzo; Gili, Josep-Maria; Chiocci, Francesco L. (Progress in oceanography, 2018)
•The effect of trawling activity on two megabenthic species were investigated along the margin of Gioia Canyon.•The abundance of the bamboo-coral Isidella elongata was lower in areas exposed to higher trawling intensity.•Diffuse presence of epibionts on I. elongata suggests stressful conditions related to trawling.•Relatively high abundances of the sea pen Funiculina quadrangularis occurred in areas with intermediate trawling effort.•Vulnerability to bottom trawling can be different for the two species. The impacts of fishing activities on ecosystems represent an acknowledged environmental issue, especially considering the increasing demands for the conservation of biodiversity. Submarine canyons are complex environments that can harbor high biodiversity of benthic ecosystems and high biomass of fish species, thus representing preferential fishing areas for bottom trawling fleets. The effects of bottom trawling on the benthic epifauna were investigated over the soft-bottom margins of the Gioia Canyon (Southeastern Tyrrhenian Sea) by means of quantitative analysis of Remote Operated Vehicle (ROV) video transects and compared with the recent pattern of trawling intensity, reconstructed through processing of data collected with the Vessel Monitoring System (VMS). Four ROV transects were then performed at 320–540 m depth in areas affected by different trawling pressure. The analysis was focused on the bamboo coral Isidella elongata and the sea pen Funiculina quadrangularis, which are considered indicator taxa of Vulnerable Marine Ecosystems (VMEs) and relevant in terms of sustainable management priorities. I. elongata only occurred at the two deeper stations, below 400 m depth. This species showed a clear relationship with trawling intensity, since its abundance was significantly higher under low trawling intensity, where coexistence of large (>20 cm height) and small colonies was observed. The relatively high prevalence of small colonies in areas exposed to higher trawling effort was interpreted as a consequence of the trawling activity that removed the larger colonies. However, the frequent occurrence of dead colonies and the diffuse presence of epibionts (e.g. the anemone Amphianthus dohrnii and the hydroid Clytia linearis) on living colonies indicate stressful conditions for I. elongata even in areas where trawling intensity was lower. Conversely, the relationship between trawling intensity and species abundance was not straightforward for F. quadrangularis; despite the lowest abundance of this species was recorded in areas subject to high trawling intensity, relatively high abundances were observed in areas with intermediate trawling effort. Although such distribution may be driven by other environmental factors, it suggests that vulnerability to bottom trawling can be different for the two species.